Examining mental health clinical placement quality using a self-determination theory approach. (April 2020) - Perlman, Dana; Patterson, Christopher; Moxham, Lorna; Burns, Shawn
Abstract: Nursing clinical placements provide a unique opportunity for students to develop and hone the skills and knowledge that will be used upon graduation in their future professional practice. There is an on-going inquiry into elements that may facilitate better leaning outcomes in a variety of teaching and learning settings, including clinical experiences. Using a Self-Determination Theory approach, this study examined whether undergraduate nursing students would benefit from immersion in an autonomy-supportive clinical setting. Using a two-group pre and post-test design, students were classified into either an autonomy-supportive or comparison clinical placement cohort and measured on their learning using the Mental Health Clinical Placement Survey. Results of a repeated measures multivariate analysis of variance indicated a significant difference on some of the measures of learning housed within the Mental Health Clinical Placement Survey with students in the autonomy-supportive group reporting higher scores at the post-test time point. Findings support the value that teaching and learning in an autonomy-supportive setting has, on the skills and educational development of students.